Polymerase chain reaction for diagnosis of genital herpes in a genitourinary medicine clinic - Scoular, A (BMJ Group, 2002)
Background: Polymerase chain reaction (PCR) has well established advantages over culture for diagnosis of herpes viruses, but its technical complexity has limited its widespread application. However, recent methodological advances have rendered PCR more applicable to routine practice. Aim: To compare automated PCR with viral culture for diagnosis of genital herpes. Methods: We studied 236 patients presenting with clinical features suggestive of genital herpes at an inner city genitourinary medicine clinic. Two swabs were taken from each patient. Cell culture and typing were performed by standard methods. Automated PCR was performed using the LightCycler instrument and the infecting viral type was determined by restriction endonuclease digestion of amplicons. Results: 109 patients (46%) had a positive test for herpes simplex virus (HSV). In 88, both PCR and culture were positive; in 21 PCR only was positive. With both detection methods, lesion duration and morphology were associated with HSV detection. Compared with culture alone, use of PCR increased sensitivity by 13.3% in specimens from vesicular lesions, by 27.4% from ulcerative lesions, and by 20.0% from crusting lesions. Conclusions: We advocate adoption of automated PCR as an efficient HSV detection and typing method for diagnosis of genital herpes in routine clinical practice. PCR allowed rapid laboratory confirmation of the diagnosis and increased the overall HSV detection rate by 24%.